VegaFS: file sharing crossing multiple domains. (6th February 2006) - Li, Wei; Liang, Jianmin; Xu, Zhiwei
We propose a file system prototype to solve the crossing domain problem, which is a great challenge for full sharing of file resources in grid environments. In our prototype, we adopted the public key in native file systems to detach file systems from administrative domains entirely. Our methods bring several benefits to the design of grid file systems such as cross-domain file access abilities, scalabilities, fine-grained dynamic access control mechanisms and better securities.